National Character Education Policy in Law Number 23 0f 2019 - Muria Putriana; Matin Matin; Sugiarto Sugiarto; Tjetjep Darmawan (AL-ISHLAH: Jurnal Pendidikan, 2021)
The study aimed to understand the value of national character education in Law number 23 of 2019. The policy of developing character values through the Act is related to strengthening national character. The method used qualitative descriptive. Data were collected through observation, interviews, and documentation. At the same time, the data analysis technique is presented in the form of narrative text through procedures, namely coding, data reduction, data presentation, data triangulation, drawing conclusions, and data analysis. The results show that there are thirteen character education values found in Law number 23 of 2019. Eleven character values are relevant to the character values conceptualized in the Indonesian education curriculum, and two new values are the values of patriotism and the spirit of Pancasila. The implications found are related to understanding the concept of character values by the diversity of Indonesian society